Membangun Masyarakat Sejahtera: Implementasi Anjuran Peduli Sosial Dalam Al-Qur’an - Nufus, M. Khoirun; Lailatul Istnaini Musthofiyah; Aris Saputra Ramadhan; Wildan Syifaunnajah; Ana Rahmawati (Indonesian Journal Publisher, 2025)
The Qur'an, as the holy book of Muslims, contains various teachings that regulate human life, including social aspects. The recommendation to care for society is one of the important themes raised in several chapters, such as Al-Fajr, Al-Ma'un, Al-Baqarah, and Al-Isra. Surah Al-Fajr (89:15-18) These verses criticize the attitude of humans who feel noble because of wealth. The Qur'an reminds us that wealth is only a test and trial from Allah SWT. The correct attitude is to be grateful for the blessings given and to use wealth for good, including helping those in need. Surah Al-Ma'un (107:2-3) This verse condemns the attitude of people who rebuke orphans. The Qur'an emphasizes that caring and loving attitudes towards orphans are an obligation for every Muslim. Surah Al-Baqarah (2:254, 261) Verse 254 emphasizes the importance of spending wealth in the way of Allah SWT, including to help the poor and those in need. Verse 261 teaches about zakat, which is the obligation for every Muslim to spend some of his wealth to help the poor, needy, and other groups. Surah Al-Isra (17:26-27) This verse teaches about the importance of being good to parents, relatives, and neighbors. The Qur'an encourages humans to build harmonious relationships with others, respect each other, and help each other.